2017
DOI: 10.5902/1980509827733
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Regeneração Natural Em Área De Restauração Ecológica E Mata Ciliar De Referência

Abstract: RESUMOÁreas ribeirinhas são foco recorrente de restauração ecológica, devido a sua importância para a manutenção de serviços ecossistêmicos. Entretanto, poucos estudos têm de fato avaliado o sucesso de intervenções ativas em restaurar funções ou processos ecossistêmicos. A regeneração natural é um processo sucessional, cuja avaliação pode indicar o estado e o potencial de resiliência do ecossistema em áreas sob restauração. O presente estudo comparou padrões de regeneração natural de uma área de restauração ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
6
0
8
Order By: Relevance
“…In the case of tree forest species, Fonseca et al (2017) demonstrated in their studies that seedlings of native species of Tapirira guianensis Aubl., Genipa americana L., Cedrela fissilis Vell., Hymeneae courbaril L., Handroanthus serratifolius (AH Gentry) S. Grose and Inga cylindrica (Vell.) Mart.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of tree forest species, Fonseca et al (2017) demonstrated in their studies that seedlings of native species of Tapirira guianensis Aubl., Genipa americana L., Cedrela fissilis Vell., Hymeneae courbaril L., Handroanthus serratifolius (AH Gentry) S. Grose and Inga cylindrica (Vell.) Mart.…”
Section: Resultsmentioning
confidence: 99%
“…This can be seen in the results of Fonseca et al (2017), who demonstrated that planting seedlings of native species with hydrogel in the driest season of the year showed a 15% lower mortality than those seedlings planted without the use of the polymer.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Em restaurações florestais, a introdução de espécies é geralmente feita por plantio de mudas. Um dos objetivos dessa etapa é atrair dispersores e estabelecer espécies lenhosas a partir da melhoria das condições de sombreamento e temperatura nessas áreas (Society for Ecological Restoration, 2004;Holl, 2013;Fonseca et al, 2017).…”
Section: Introductionunclassified
“…Thus, natural regeneration can be seen as a dynamic process, capable of providing information about the behavior, maintenance and how the incoming species are established in forest ecosystems [8,9]. In addition, natural regeneration can also be analyzed as a process of advancement or resumption of forest succession, which makes it possible to establish relationships between patterns of composition and diversity of species, with ecological processes that are associated with the dynamics of succession of communities [10,11,12].…”
Section: Introductionmentioning
confidence: 99%